Joint formation mechanism of high depth-to-width ratio friction stir welding. Issue 7 (July 2019) - Huang, Yongxian; Xie, Yuming; Meng, Xiangchen; Li, Junchen; Zhou, Li
Abstract: High depth-to-width ratio friction stir welding is an attractive method for the joining demands of aluminum profiles, which is sparked with its extremely low heat input and high mechanical performance. In this study, the joint formation mechanism was studied by a numerical model of plastic flow combined with experimental approaches. A fluid-solid-interaction algorithm was proposed to establish the coupling model, and the material to be welded was treated as non-Newtonian fluid. The thread structure and the milling facets on tool pin promoted drastic turbulence of material. The thread structure converged the plasticized material by its inclined plane, and then drove the attached material to refill the welds. The milling facets brought about the periodic dynamic material flow. The thread structure and the milling facets increased the strain rate greatly under the extremely low heat input, which avoided the welding defects. The condition of the peak temperature of 648 K and the strain rate of 151 s −1 attributed to the lowest coarsening degree of precipitate. The tensile strength of the joint reached 265 MPa, equivalent to 86% of base material. The amelioration via the material flow model inhibits the welding defects and optimizes the parameter intervals, providing references to extracting process-structure-property linkages for friction stir welding.